A RARE ENDOCRINE CASE REPORT OF KALLMANN SYNDROME - Nasir Mahmood (Journal of University Medical & Dental College, 2017)
ABSTRACT: Kallmann syndrome is a rare disorder of secondary hypogonadism with or without anosmia/ hyposmia due to abnormal migration of gonadotrophin releasing hormone producing neurons in hypothalamus. We report a case of 28 year old male who presented to us with absent secondary sexual characteristics i.e absent beard and moustaches along with small testicular volume and micropenis. Examination revealed eunuchoid habitus , hyposmia , absent facial hair, tanner stage2 testicular volume , penile length and pubic hair. Investigations showed hypogonadotrophic hypogonadism , normal ultrasound abdomen, osteoporosis on DXA scan, azoospermia in semen analysis and hypoplastic olfactory bulb on MRI Brain which all strengthen our diagnosis of kallmann syndrome. We started treatment with parenteral Androgen i.e Testosterone. After 06 month of treatment with testosterone , he started to have facial hair. We are monitoring the patient and our plan is to put him on Human chorionic gonadotrophin once he will desire fertility.